Strangulated direct inguinal hernia with intraperitoneal perforation - Bakhteyar, Md Asjad Karim; Kumar, Binod; Kumar, Sushil (International Surgery Journal, 2017)
Usually direct inguinal hernia doesn’t present as strangulation or incarceration as compared to indirect inguinal hernia because of earlier has wider neck. A patient of recurrent direct inguinal hernia presents as intra-scrotal gangrene and intra-peritoneal perforation. We reported a case of 65 years old male presented with septicemia and right sided strangulated direct hernia. On exploration through inguino scrotal incision and mid line laparotomy, gangrenous loop was found in scrotum and perforation was found in intra-peritoneal part of small intestine. Resection-anastomosis was done for both the parts of intestine. Inguinal Incision was closed by posterior wall closure and modified Bassini’s herniorraphy. Abdomen was closed in layers with brain. Long standing direct hernia may present as strangulation or incarceration specially in elderly but perforation and gangrene of intra-peritoneal part of small intestine is very rare.